TYPOLOGIES OF COPRODUCTION OF THE PUBLIC GOOD: STATE OF THE ART AND RESEARCH AGENDA - Gouveia Júnior, Antonio (2023)
The purpose of this article is to present the state of the art on the types of coproduction of the public good and how they can be used in the public policy cycle. The research used the Systematic Literature Review (RSL) method and the selected studies were analyzed in their entirety via categorical content analysis, aiming to identify different types of co-production. The analysis of the studies focused on the following categories: objective of the study, types of co-production and main results. The results show the variety and complexity of the co-production models, as well as not having a single model or typology for co-production. Studying the types of co-production is relevant in understanding the co-production process and its consequences. Knowing the typologies can be useful to managers, since it allows them to select those aligned with the objectives proposed by the Public Administration, working as a management strategy and contributing to improvements in the public policy cycle.